Prevalence of delivery mode in an Italian nationwide cohort with celiac disease: a SIGENP multicenter retrospective study (the CD-deliver-IT) - Donatella Iorfida; Francesco Valitutti; Annarita Vestri; Grazia D'Adamo; Tiziana Passaro; Marco Crocco; Federica Malerba; Alice Monzani; Ivana Rabbone; Licia Pensabene; Laura Giancotti; Francesco Graziano; et al. (BMC, 2024)
Abstract Background Studies have indicated an association between cesarean section (CS), especially elective CS, and an increased risk of celiac disease (CD), but the conclusions of other studies are contradictory. The primary aim of this study (CD-deliver-IT) was to evaluate the rate of CS in a large population of CD patients throughout Italy.  Methods This national multicenter retrospective study was conducted between December 2020 and November 2021. The coordinating center was the Pediatric Gastroenterology and Liver Unit of Policlinico Umberto I, Sapienza, University of Rome, Lazio, Italy. Eleven other referral centers for CD have participated to the study. Each center has collected data on mode of delivery and perinatal period of all CD patients referring to the center in the last 40 years. Results Out of 3,259 CD patients recruited in different Italian regions, data on the mode of delivery were obtained from 3,234. One thousand nine hundred forty-one (1,941) patients (60%) were born vaginally and 1,293 (40%) by CS (8.3% emergency CS, 30.1% planned CS, 1.5% undefined CS). A statistically significant difference was found comparing median age at time of CD diagnosis of patients who were born by emergency CS (4 years, CI 95% 3.40-4.59), planned CS (7 years, CI 95% 6.02-7.97) and vaginal delivery (6 years, CI 95% 5.62-6.37) (log rank p < 0.0001). Conclusions This is the first Italian multicenter study aiming at evaluating the rate of CS in a large population of CD patients through Italy. The CS rate found in our CD patients is higher than rates reported in the general population over the last 40 years and emergency CS seems to be associated with an earlier onset of CD compared to vaginal delivery or elective CS in our large nationwide retrospective cohort. This suggests a potential role of the mode of delivery on the risk of developing CD and on its age of onset, but it is more likely that it works in concert with other perinatal factors. Further prospective studies on other perinatal factors potentially influencing gut microbiota are awaited in order to address heavy conflicting evidence reaming in this research field.